Blueberry Juice Antioxidants Protect Osteogenic Activity against Oxidative Stress and Improve Long-Term Activation of the Mineralization Process in Human Osteoblast-Like SaOS-2 Cells: Involvement of SIRT1 - Vladana Domazetovic; Gemma Marcucci; Irene Falsetti; Anna Rita Bilia; Maria Teresa Vincenzini; Maria Luisa Brandi; Teresa Iantomasi (Antioxidants, 2020)
Diets rich in fruits and vegetables with many antioxidants can be very important in the prevention and treatment of osteoporosis. Studies show that oxidative stress, often due to lack of antioxidants, is involved in alteration of bone remodeling and reduction in bone density. This study demonstrates in human osteoblast-like SaOS-2 cells that blueberry juice (BJ), containing 7.5 or 15 μg∙mL−1 total soluble polyphenols (TSP), is able to prevent the inhibition of osteogenic differentiation and the mineralization process due to oxidative stress induced by glutathione depletion. This situation mimics a metabolic condition of oxidative stress that may occur during estrogen deficiency. The effect of BJ phytochemicals occurs through redox- and non-redox-regulated mechanisms. BJ protects from oxidative damage factors related to bone remodeling and bone formation, such as alkaline phosphatase and Runt-related transcription factor 2. It upregulates these factors by activation of sirtuin type 1 deacetylase expression, a possible molecular target for anti-osteoporotic drugs. Quantitative analysis of TSP in BJ shows high levels of anthocyanins with high antioxidant capacity and bioavailability. These novel data may be important to elucidate the molecular and cellular beneficial effects of blueberry polyphenols on bone regeneration, and they suggest their use as a dietary supplement for osteoporosis prevention and therapies.